NANOSTRUCTURAL PROCESSES OF MELTING, CRYSTALLIZATION AND MODIFYINGS OF METALS - V. Yu. Stetsenko (Литьë и металлургия, 2015)
It is shown that melting, crystallization and modifying of metals are difficult nanostructural processes. The nanocrystals and atoms of metals, the centers of crystallization of dendrites, surface-active elements, gases modifying elements, poorly soluble impurity elements in solid metal generally participate in these processes. Their activity and intensity of abstrаction of heat during crystallization define structure of metal